Artificial Intelligence in Higher Education: Opportunities and Challenges in India - Dubey, Sanjiva (Global journal of Business and Integral Security, 2024)
The study focuses on the factors influencing the use of Artificial Intelligence in Education (AIED) in higher education institutions (HEIs) in India. The Indian higher education system continues to face a number of perennial problems which can be summed up as follows: • rigid academic calendar, • low employment rate of fresh graduates, and • ineffective and outmoded lecture-tutorial methods. AIED offers an interesting chance to resolve these questions by increasing teachers’ efficiency, individualization of learning processes, and decreasing bureaucratic demands. However, to the best of the knowledge of the authors, few studies have explored the use of AI technologies in Indian HEIs. This research will try to assess the effects of AI in the teaching, learning, and administrative functions in the selected Indian HEIs and the determining factors of AI integration. The research specifically examines the following: • AI in current higher education, • advantages, and problems of AI usage, • impact on students’ performance, and • further AI trends in learning. The method of the research is a quantitative questionnaire intended to collect data from 200 participants from various educational establishments, AI specialists, and Ed-tech firms. The examination employs validated survey instruments from previous literature; the constructs include Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Technology Readiness, and Knowledge about AI. The data collection technique used was an online survey administered to the participants, and content validity was established using a pre-test while the reliability test was conducted using a pilot test. The Data collected is analyzed by Structural Equation Modelling (SEM) which tests both measurement and structural models to test the relationships between the observed and the latent variables. The analysis shows that Technology Readiness acts as a mediator, which helps to strengthen the positive associations of the components of UTAUT with the behavioral intention to employ AIED. In the same way, the knowledge level of an individual moderates these relationships and affects the individual’s perception of the adoption of AI in education. The research provides a way forward to enable the integration of AI in the Indian higher education system and the importance of focusing on its readiness and awareness amongst the stakeholders. It adds to the existing literature on AI in Indian HEIs and suggests recommendations for AI utilization to counter existing educational issues and improve students’ learning opportunities.